Pernikahan Usia Dini Dalam Perspektif Hukum Islam Dan Hukum Positif Indonesia: Rekonstruksi Batas Usia Perkawinan Berbasis Maqāṣid Al-Syarī'ah Dan Perlindungan Hak Anak - Melin Manik; Aripa Syawalia; Putri Azri Sipahutar; Zahra Balqis Ananda Lubis; Mutiara Khalishah; Rahmad Hidayat (Yayasan Dar Arrisyah Indonesia, 2024)
Child marriage remains one of the most persistent legal and social challenges in Indonesia despite the enactment of Law Number 16 of 2019, which equalizes the minimum marriage age for both men and women at nineteen years. The increasing number of marriage dispensations indicates that legal reform alone has not effectively prevented child marriage. Previous studies have predominantly discussed early marriage from either normative Islamic jurisprudence or statutory perspectives, while limited attention has been devoted to integrating Islamic legal objectives (maqāṣid al-sharī'ah) with child protection principles in evaluating the effectiveness of marriage age regulation. This study aims to analyze the compatibility between Islamic law and Indonesian marriage law regarding the minimum marriage age and to formulate a reconstruction of legal policy based on maqāṣid al-sharī'ah. This research employs normative legal research using statutory, conceptual, and comparative approaches. Primary legal materials consist of Law Number 16 of 2019, the Compilation of Islamic Law, Constitutional Court Decision Number 22/PUU-XV/2017, and relevant judicial decisions. Secondary legal materials include classical Islamic legal literature, contemporary scholarly works, and international journal articles. The findings demonstrate that Islamic law does not prescribe a numerical minimum marriage age but emphasizes maturity (rushd), capability (istiṭā‘ah), and public welfare (maṣlaḥah). Therefore, Indonesia's minimum marriage age policy is consistent with the objectives of Islamic law in protecting religion, life, intellect, lineage, and property. Nevertheless, the broad application of marriage dispensations weakens the effectiveness of legal protection for children. This study proposes strengthening substantive judicial standards for marriage dispensation, integrating reproductive health education, and harmonizing religious values with child protection policies as a comprehensive strategy to prevent child marriage.